2023
DOI: 10.3889/oamjms.2023.10478
|View full text |Cite
|
Sign up to set email alerts
|

Firmicutes/Bacteroidetes Ratio of Gut Microbiota and Its Relationships with Clinical Parameters of Type 2 Diabetes Mellitus: A Systematic Review

Abstract: BACKGROUND: Type 2 diabetes mellitus (T2DM) is a global health problem with multifactorial etiopathogenesis. Recent studies show gut microbiota dysbiosis that plays a crucial role in pathogenesis and complications of T2DM. Firmicutes and Bacteroidetes phylum ratio (F/B ratio) is one of the markers for gut microbiota dysbiosis which remains to be investigated in recent decades. AIM: The present study summarized the correlation between B/F ratio with some clinical parameters of T2DM. METHODS: A systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Based on previous extensive assessment of microbiota studies, other studies have shown that it is difficult to associate the Firmicutes/Bacteroidetes ratio with a determined health status [40,46]. A clear suggestion was to explore compositional changes at the family, genus, or species level, which might be more relevant than the phyla-based Firmicutes/Bacteroidetes ratio [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous extensive assessment of microbiota studies, other studies have shown that it is difficult to associate the Firmicutes/Bacteroidetes ratio with a determined health status [40,46]. A clear suggestion was to explore compositional changes at the family, genus, or species level, which might be more relevant than the phyla-based Firmicutes/Bacteroidetes ratio [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistencies with regards to differences in the alpha/beta-diversity or Firmicutes/Bacteroidetes (F/B) ratio are amongst the most common. The F/B ratio is widely accepted as a sign of intestinal homeostasis and overall gut health, and its alteration has been previously described in inflammatory bowel diseases [ 33 , 34 ] as well as metabolic disorders [ 35 , 36 , 37 ]. However, the precise implications or effects of F/B imbalance on disease progression and patient outcome in ALS remain unknown due to conflicting results amongst current profiling studies.…”
Section: Evidence Of Gut Dysbiosis In Human Amyotrophic Lateral Scler...mentioning
confidence: 99%
“…The ratio is reported to be elevated in obesity [20] and inflammatory bowel disease [21] suggesting a potential link to gut dysbiosis. In type 2 diabetes, the ratio varies and is associated with different clinical parameters such as diet, lifestyle, genetics and environmental factors [22,23]. Alterations of the gut-microbiota brought upon by 'western diets' has been postulated to exacerbate inflammatory diseases [4].…”
Section: Figurementioning
confidence: 99%